Hypoxia Induced Changes of Exosome Cargo and Subsequent Biological Effects - Jiang, Hongxia; Zhao, Hanqiu; Zhang, Mengzhe; He, Yuanzhou; Li, Xiaochen; Xu, Yongjian; Liu, Xiansheng (Frontiers in Immunology, 2022)
Exosomes are small extracellular vesicles that are secreted by almost all types of cells and exist in almost all extracellular spaces. As an important mediator of intercellular communication, exosomes encapsulate the miRNA, lncRNA, cirRNA, mRNA, cytokine, enzyme, lipid, and other components from the cytoplasm into its closed single membrane structure and transfer them to recipient units in an autocrine, paracrine, or endocrine manner. Hypoxia is a state of low oxygen tension and is involved in many pathological processes. Hypoxia influences the size, quantity, and expression of exosome cargos. Exosomes derived from hypoxic tumor cells transfer genetics, proteins, and lipids to the recipient units to exert pleiotropic effects. Different donor cells produce different cargo contents, target different recipient units and lead to different biological effects. Hypoxic exosomes derived from tumor cells uptaken by normoxic tumor cells lead to promoted proliferation, migration, and invasion; uptaken by extracellular space or liver lead to promoted metastasis; uptaken by endothelial cells lead to promoted angiogenesis; uptaken by immune cells lead to promoted macrophage polarization and changed tumor immune microenvironment. In addition to various types of tumors, hypoxic exosomes also participate in the development of diseases in the cardiovascular system, neuron system, respiratory system, hematology system, endocrine system, urinary system, reproduction system, and skeletomuscular system. Understanding the special characteristics of hypoxic exosomes provide new insight into elaborating the pathogenesis of hypoxia related disease. This review summarizes hypoxia induced cargo changes and the biological effects of hypoxic exosomes in tumors and non-malignant diseases in different systems.